The Development of Basic Technical Skills Training Playing Soccer Model Soccer School - Emral; Aldha Yudi, Alex; Komarudin; Bagdja Ijatna, Satia (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to produce the product "Development of Basic Technical Skills Training Models Playing Soccer Tabing Padang Football School Students," which can be used by students or athletes under the age of 14 years. The research method used is research and development. This is indicated by several assessments that have been carried out by material experts, media experts, trainers, and group trials. The final results of the product assessment by the material experts showed that the learning module was declared "feasible" with a percentage of 84.89%. and the final results of the product evaluation by the media experts showed "feasible" with a percentage of 87.96%, and the final results of the product evaluation by the SSB trainers showed "feasible" with a percentage of 85.16%. In the results of the small group trial, the results obtained were "feasible" with a percentage of 88.44%, and the results of the large group trials obtained "decent" results with a percentage of 87.64%. Based on the results of small group trials and large group trials or field trials as well as model effectiveness tests, it is known that the product model of basic soccer skill training developed in this study is considered to meet the requirements and is effective for socializing and applying in soccer practice so that books and video products are feasibly used for ages 13-14 years.